The Clarion Call of the COVID-19 Pandemic: How Medical Education Can Mitigate Racial and Ethnic Disparities. (27th April 2021) - Prince, Andrew D.P.; Green, Alexander R.; Brown, David J.; Thompson, Dana M.; Neblett, Enrique W.; Nathan, Cherie-Ann; Carethers, John M.; Gee, Rebekah E.; Gruppen, Larry D.; Mangrulkar, Rajesh S.; Brenner, Michael J.
Abstract : Public health crises palpably demonstrate how social determinants of health have led to disparate health outcomes. The staggering mortality rates among African Americans, Native Americans, and Latinx Americans during the COVID-19 pandemic have revealed how recalcitrant structural inequities can exacerbate disparities and render not just individuals but whole communities acutely vulnerable. While medical curricula that educate students about disparities are vital in rousing awareness, it is experience that is most likely to instill passion for change. The authors first consider the roots of health care disparities in relation to the current pandemic. Then, they examine the importance of salient learning experiences that may inspire a commitment to championing social justice. Experiences in diverse communities can imbue medical students with a desire for lifelong learning and advocacy. The authors introduce a 3-pillar framework that consists of trust building, structural competency, and cultural humility. They discuss how these pillars should underpin educational efforts to improve social determinants of health. Effecting systemic change requires passion and resolve; therefore, perseverance in such efforts is predicated on learners caring about the structural inequities in housing, education, economic stability, and neighborhoods—all of which influence the health of individuals and communities.